2009
DOI: 10.5688/aj7307123
|View full text |Cite
|
Sign up to set email alerts
|

College/School of Pharmacy Affiliation and Community Pharmacies' Involvement in Public Health Activities

Abstract: Objectives. To examine the relationship between pharmacy college/school affiliation and community pharmacies' involvement in immunization and emergency preparedness activities. Methods. Telephone interviews were completed with 1,704 community pharmacies randomly sampled from 17 states to determine the pharmacies' involvement in immunization promotion, vaccine distribution, in-house immunization delivery, and health emergency preparedness and response, affiliation with college/school of pharmacy, and selected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Again, in a US study[70] that investigated the benefits of college/school of pharmacy being affiliated with community pharmacies, it was noted that pharmacy college/school‐affiliated community pharmacies were more likely than non‐affiliated pharmacies to participate in immunisation and emergency preparedness. Furthermore, in a US intervention study[71] it was observed that through the APPE and health promotion interventions, women's awareness about health issues was enhanced, while students were also guided to achieve the desired curricular outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Again, in a US study[70] that investigated the benefits of college/school of pharmacy being affiliated with community pharmacies, it was noted that pharmacy college/school‐affiliated community pharmacies were more likely than non‐affiliated pharmacies to participate in immunisation and emergency preparedness. Furthermore, in a US intervention study[71] it was observed that through the APPE and health promotion interventions, women's awareness about health issues was enhanced, while students were also guided to achieve the desired curricular outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…41,45 These experiences allow pharmacy students to gain clinical exposure to immunization services while strengthening the connection between pharmacy schools and the surrounding community pharmacies. 53 Initiatives to involve nurses and physicians in PBIS may further promote collaborative approaches to improving primary and preventative care services for patients.…”
Section: Discussionmentioning
confidence: 99%
“…43,51 Similarly, immunization-certified pharmacists were much more likely to be involved in some aspect of immunization (99%) than noncertified pharmacists (24%). 48 The presence of one or more immunization-certified pharmacists was correlated with the pharmacy offering immunization services, 53 and with a transition from no or outsourced services to a pharmacist-delivered immunization system. 47,54 However, the number of years a pharmacist has been practicing may be associated with immunization participation.…”
Section: Feasibilitymentioning
confidence: 99%
“…5,6 In our review of the pharmacy education literature, we found several articles discussing education of pharmacy students to care for patients with specific diseases or conditions such as asthma, diabetes, hypertension, or to provide care in specific circumstances, ie, disaster preparedness or emergency contraception. [7][8][9][10][11] These articles deal more with chronic disease follow-up, ie, asthma, diabetes, or hypertension, than management of emergency situations. [7][8][9] Since 2007 the Université catholique de Louvain has provided a first aid course for pharmacy students during the first semester of their third year.…”
Section: Introductionmentioning
confidence: 99%